병원직원의 노사관계 형태 인식 - 최윤미 (연세대학교 보건대학원, 1990)
[한글] 의료조직에서의 노사문제는 최근에 중요한 관심사가 되었는데 이는 1987년 6월 29일 이후 정치적 변환기를 맞아 분출된 산업체의 노동운동이 병원계에도 확산되었기 때문이다. 여러형태의 정치, 경제, 사회 등 환경의 급격한 변화 속에서 공익사업체인 병원의 직원들을 대상으로 노사관계 형태에 대한 인식, 노조 및 사용자에 대한 인식, 그리고 노조 및 사용자에 대한 인식과 노사관계 형태와의 관련성을 알아보고자 하였다. 연구를 위하여 임의로 선정된 2개의 대학병원과 2개의 국공립병원 직원중 직종별로 무작위 추출하여 298명에 대해 1990년 5월 27일부터 5월 30일 사이에 설문조사를 실시하였다. 결과는 다음과 같다. 1. 응답자의 학력, 직종, 노조가입여부가 노사관계 형태에 대한 인식과 통계학적으로 유의하였다. 2. 노조에 가입한 사람이 노조에 가입하지 않은 사람보다 노조에 대한 인식이 긍정적이고, 설립시기별로 보아 1987년 7월을 전후하여 과거에 노조가 설립된 병원보다 그후에 노조가 설립된 병원의 직원이 노조를 긍정적으로 인식하고 있었다. 3. 단체협약에 대한 인식은 연령, 학력, 결혼상태, 직종, 노조가입여부와 유의한 상관관계가 있었으며 노조가 최근에 설립된 병원에서는 부정적인 응답이 많았다. 4. 사용자에 대한 인식은 학력, 직종, 직위, 노조가입 여부와 통계학적으로 유의하였으며, 노조설립이 1987년 이후에 이루어진 병원에서는 부정적인 응답이 많았다. 5. 노조가 1987년 이후에 설립된 병원의 직원은 갈등형과 무장휴전형에 많이 응답하였고, 그 이전에 설립된 병원은 적응형과 협동형에 많이 응답하였는데 이는 통계적으로 유의하였다. 6. 노사관계 형태는 노조에 대한 인식이 긍정적일수록 갈등형이나 무장휴전형으로, 단체협약에 대한 인식이 긍정적일수록 협동형으로, 사용자에 대한 인식이 긍정적일수록 적응형과 협동형으로 나타났는데 이는 통계적으로 유의하였다. A study on hospital worker's perception on the labor relations Yun Mi Choi Graduate School of Health Science and Management, Yonsei University (Directed by Professor Kyu Sik Lee) Until July 1987, the problems of labor relations in the health service industry have not gained widespread attention. Little research has been conducted on the labor relations in the field of health industry. Most of the research on the labor relations has focused primarily on industry. The present study has a concern to identify and describe the predominant perception of hospitals workers on the labor relations. The research method used in this study was self-administered questionnaire responses. It was designed to measure the degree of agreement with each of five type of labor relations. (Conflict, Armed Truce, Power Bargaining, Accommodation. Cooperation). The pre-test was done by 20 hospital workers from May 23 to May 24, 1990. After per-test, the final questionnaire was completed. The main survey was conducted from May 27 to May 30, 1990. The Questionnaire delivered with to 370 hospital worker. A total of 315 sampled persons responed. The Response rate was 85.1% and the data were analyzed by cross tables. The results were as follows : 1. The variable with statistically significant with perception on a type of labor relation are : the educational level, type of work and whether join a union or not. 2. Those who join a union has more positively responded to the perception on a type of labor relation than one not join. 3. Perception on collective agreement was significant correlation with age, educational level, marital status, type of work and joining a union or not. 4. Perception about a manager was statistically significant with educational level, type of work, job status, joining a union or not. 5. The worker of hospital which union is organized since truly 1987, negatively responded to the perception on the manager and collective agreement. But they positively perceived on the labor union. 6. The worker of hospital which union is organized recently perceived that labor relation is "Conflict" or "Armed-Truce", while the worker of hospital which union is organized before truly 1987 perceived that labor relation is "Accommodation" or "Cooperation". [영문] Until July 1987, the problems of labor relations in the health service industry have not gained widespread attention. Little research has been conducted on the labor relations in the field of health industry. Most of the research on the labor relations has focused primarily on industry. The present study has a concern to identify and describe the predominant perception of hospitals workers on the labor relations. The research method used in this study was self-administered questionnaire responses. It was designed to measure the degree of agreement with each of five type of labor relations. (Conflict, Armed Truce, Power Bargaining, Accommodation. Cooperation). The pre-test was done by 20 hospital workers from May 23 to May 24, 1990. After per-test, the final questionnaire was completed. The main survey was conducted from May 27 to May 30, 1990. The Questionnaire delivered with to 370 hospital worker. A total of 315 sampled persons responed. The Response rate was 85.1% and the data were analyzed by cross tables. The results were as follows : 1. The variable with statistically significant with perception on a type of labor relation are : the educational level, type of work and whether join a union or not. 2. Those who join a union has more positively responded to the perception on a type of labor relation than one not join. 3. Perception on collective agreement was significant correlation with age, educational level, marital status, type of work and joining a union or not. 4. Perception about a manager was statistically significant with educational level, type of work, job status, joining a union or not. 5. The worker of hospital which union is organized since truly 1987, negatively responded to the perception on the manager and collective agreement. But they positively perceived on the labor union. 6. The worker of hospital which union is organized recently perceived that labor relation is "Conflict" or "Armed-Truce", while the worker of hospital which union is organized before truly 1987 perceived that labor relation is "Accommodation" or "Cooperation".
병원행정학과/석사